Die gebruik van die Ou Testament in die volkslewe: ’n ondersoek onder predikante en ander lidmate van die Gereformeerde Kerke in Suid-Afrika - Helberg, J.L.; Van Rooy, H.F. (AOSIS, 1995)
The aim of this study was to determine the use of the Old Testament by members of the Gereformeerde Kerke in Suid-Afrika and the way in which the Old Testament is applied to the contemporary situation. An empirical study was undertaken to determine the approach of members of these churches to the Old Testament. In the first part of the paper issues necessary to evaluate the empirical study are discussed, while the second part presents the results of the empirical study. It is clear from the survey that the Old Testament is not used to the same extent as the New Testament by the ministers and other members of these churches. The views of the ministers on the application of the Old Testament to the situation of the Afrikaners are more nuanced than those of the other members of these churches.